Scientific examination of questioned documents - Seaman Kelly, Jan; Lindblom, Brian S. (Boca Raton, FL : CRC/Taylor & Francis, 2006)
An essential guide for the novice and the seasoned professional, this authoritative and comprehensive book is also an informative reference for the layperson who is interested in the subject. Featuring chapters written by several forensic document examination experts, this new edition is extensively revised to reflect post-1982 developments. Since that time, new avenues of written communication have emerged, as well as the proliferation of desktop computers and printers. Both of these factors have strongly impacted the nature of the examinations performed and the methodologies used. The book thoroughly explores the complexities involved in keeping current with these developments and does so, in some instances, aided by the presentation of a variety of documents and case studies. Discussion topics include infra-red exams, the use of computer hardware and software in document examination, and innovative chart making techniques. New chapters cover computer printer technologies, facsimiles, techniques for the detection of digitally manipulated documents and photocopies, ASTM standards for reporting conclusions along with advanced examination techniques. Updated chapters include expanded discussion of ESDA and other analytical tools, document dating, modern stamp making technology, and more.
About the editors/authors -- Contributors -- Preface -- Acknowledgments -- 1. Organization and content of book -- 2. What is forensic document examination -- 3. A forensic document examiners training -- 4. Care and handling of documents -- 5. Work notes -- 6. The Daubert era -- 7. Conclusions and guidelines for handwriting comparison -- 8. Identification of handwriting -- 9. Identification of signatures -- 10. Identification of hand printing and numerals -- 11. Disguise in hand printing and numerals -- 12. Preparation and collection of signatures and handwriting standards -- 13. Pens and pencils -- 14. Typography -- 15. Typewriters -- 16. The examination of computer-generated documents -- 17. Photocopiers -- 18. Facsimile machines -- 19. Manipulated photocopies, faxes, and computer-printed documents -- 20. Rubber stamps -- 21. Checkwriters -- 22. Staples -- 23. Conventional printing processes -- 24. Paper examinations -- 25. Carbonless paper -- 26. Accidental markings and indented writing on a document -- 27. Alterations in documents -- 28. Multi-faceted approach -- 29. The role of indentation analysis, offsetting, and transfer -- 30. Dating by materials: identification, comparison, and examination of changes -- 31. Cameras, scanners, and image enhancement -- 32. Conclusions and guidelines -- 33. Considerations in preparing for court -- 34. Demonstrative charts -- 35. Pretrial conference -- 36. Preparation for a Daubert hearing -- 37. The untrained document expert witness -- 38. The document examiners testimony in court -- Glossary -- Index.
Includes bibliographical references and index.
Keywords: Writing -- Identification; Forgery